Power and the French Revolution: Toward a Sociology of Sovereignty - Isaac Ariail Reed (Historicka Sociologie, 2018)
In what sense was the French Revolution exceptional – a moment of potential liberation both unique and uncertain? “Exceptionality” has a specific meaning in political philosophy, and, using this meaning as a departure point, this paper develops a specifically sociological typology of states of exception – enunciative, reciprocal, and structural – grounded in a Hegelian sociology of power. The schema is useful for parsing and interpreting several of Robespierre’s most important speeches during the Revolution. This analysis leads to retheorization of modernity in the French Revolution, with specific attention to the interpretation, in Paris, of the revolution in Saint Domingue.